Economic Impact of Climate Change on the Agricultural Sector of Punjab (The Pakistan Development Review, 2010)
As back as the Industrial Revolution, anthropogenic activities namely, power generation from fossil fuels and deforestation activities have been continuously increasing the atmospheric concentration of GHGs beyond their natural limits resulting in an enhanced greenhouse effect, vis-à-vis, an increase in global temperature. The rise in temperature could be coupled with changes in rainfall pattern, rise in sea level, and frequency and severity of extreme events namely, cyclones and droughts etc. The sum of all these changes is referred to as climate change. Climate change affects economic development in many ways, especially the agrarian economies have always depended on vagaries of nature and climate. Change in temperature, precipitation averages and extreme climate events can alter yield, income, health, sociology and physical safety. Climate change is a global phenomenon and no country is immune to it. The disappearing of the Himalayan glaciers at a fast pace would increase the probability of extreme water flows, rendering it uncontrolled will bring heavy floods, loss of life, livestock, crops and infrastructural facilities in Pakistan, India, Nepal and Bangladesh. Climate change will affect all sectors of the economy not alone agricultural sector the most as well as health, forests, energy, coastal area, biodiversity and ecology all over the globe. In this connection, it will be pertinent to give the most recent events which have taken place across Asia.